Airplane Photography - Ives, Herbert Eugene, 1882-1953 (Salt Lake City, UT : Project Gutenberg, 2016)
"Airplane Photography" by Herbert Eugene Ives is a scientific publication written in the early 20th century. The book explores the evolution and principles of aerial photography, particularly its military applications during and after the Great War, while also addressing the expanding possibilities for peaceful uses. The work is designed for readers with a background in photography who are interested in the intricate relationship between airplane mechanics and photographic techniques. The opening of "Airplane Photography" sets the stage for understanding the advancements and challenges in aerial photography that arose from wartime experiences. It provides insight into the historical context, detailing the limited use of kites and balloons for aerial photography prior to WWI and how the airplane transformed reconnaissance in warfare. Ives discusses the growing reliance on photography for military intelligence and the significant innovations in photographic equipment necessitated by the unique conditions of flight, such as vibration and the need for rapid exposure times. This initial chapter outlines the fundamental principles that govern successful aerial photography, hinting at the detailed technical discussions that follow in the rest of the book. (This is an automatically generated summary.)
Release date is 2016-11-12
E-text prepared by Richard Tonsing and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Aerial photography